Mathematical Approach to Strokes as an Attractor Within Communication Dynamical System - Andonović, Beti (National and University Library of the Republic of Srpska, 2015)
Transactional Analysis as a personality theory has offered some powerful concepts to explain and improve communication between individuals. On the other hand, positive productive communication among large numbers of people, as a compound set of transactions, as an essential aspect of human survival has not been so well explained. Like the weather and other chaotic processes, group behavior is not easily understood or predicted. It has been long suspected that in large groups of people (organizations, communities, societies), positive communication has a leading role in maintaining the duration and quality of communication. It is the aim of this paper to relate the mathematics notion of dynamical systems to the compound system of communication. The postulate that strokes, a concept introduced by E. Berne as a way in which people recognize each other, and elaborated by Steiner as a way of exchanging information, is discussed as a concept that introduces stability into the functioning of large groups.